factoriser le premier membre puis résoudre l'équation.
a -3x(2x+5)=0 ,b- x²+12x=0 , C- (2x-1)*(x+1)=0

exo2: résoudre l’équation:
a- (2x-1)(x+3)=0 ,b- 3x(x-1)=5(x-1) d- 2x+3=x²+3

merci de m'aider car je ne comprend pas

1

Réponses

  • Utilisateur Brainly
2013-12-03T19:22:49+01:00
factoriser le premier membre puis résoudre l'équation. 
a -3x(2x+5)=0
x=0 ou x=-2,5

b- x²+12x=0
x=0 ou x=-12

C- (2x-1)*(x+1)=0
x=1/2 ou x=-1

exo2: résoudre l’équation:
a- (2x-1)(x+3)=0
x=1/2 ou x=-3

b- 3x(x-1)=5(x-1)
(x-1)(3x-5)=0
x=1 ou x=5/3

d- 2x+3=x²+3

x(x-2)=0
x=0 ou x=2